Effect Of Operating Complexity, Audit Tenure And Financial Distress On Audit Report Lag With The Size Of The Public Accountant Firm As The Moderating Variable - Sinta Sukma Watini; Elok Faiqoh Himmah; Anike Putri (International Journal of Business, Economics, and Social Development)
Companies listed on the IDX are required to report their financial statements in a timely manner. However, in the existing phenomenon, many companies still experience delays in financial reporting. This study aims to identify factors that influence audit report lag in Consumer cyclicals sector companies listed on the IDX for the 2017-2021 period. The dependent variable is audit report lag, the independent variables are operational difficulties, audit tenure, financial distress, and the moderating variable is the size of the KAP. This study is a type of quantitative research with multiple regression analysis methods. The data used are secondary data in the form of financial reports from the official IDX website. A sample of 175 company financial reports was taken using the purposive sampling method. Based on the results of statistical tests, it was obtained that the operational difficulty variable did not affect ARL, the audit tenure variable affected ARL, the financial distress variable affected ARL, the KAP size variable was unable to moderate the effect of operational complexity on ARL, the KAP size variable was able to moderate the effect of operational complexity on ARL and the effect of audit tenure on ARL, the KAP size variable was able to moderate the effect of financial distress on ARL, the effect of operational complexity, audit tenure and financial distress simultaneously affected ARL.